2022
DOI: 10.3390/infrastructures7050063
|View full text |Cite
|
Sign up to set email alerts
|

Corrective and Preventive Action Plan (CAPA) for Disputes in Construction Projects: A Norwegian Perspective

Abstract: The consensus in the Norwegian construction industry is that the projects are characterized by conflicts. Because unresolved disputes that reach courts take time and resources to be solved, this leads to lost productivity and high costs for all stakeholders. Of the root causes of conflicts identified previously, tender specification and contract understanding were the most significant issues. To expand on previous findings, a qualitative analysis of 58 formal, semi-structured interviews was conducted to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Clear responsibility of the contractor and the customer for improper performance of contractual obligations [85,86] Construction contracts were evaluated based on expert assessment, after the significance of the quality assurance criteria had been established. Two expert panels were used to determine the significance of the quality assurance criteria.…”
Section: R6mentioning
confidence: 99%
See 1 more Smart Citation
“…Clear responsibility of the contractor and the customer for improper performance of contractual obligations [85,86] Construction contracts were evaluated based on expert assessment, after the significance of the quality assurance criteria had been established. Two expert panels were used to determine the significance of the quality assurance criteria.…”
Section: R6mentioning
confidence: 99%
“…The causes of disputes in a construction project range from a lack of detail in the design of the structure and inadequate risk assessment when bidding for construction work, to poor communication between customers and contractors, with each possible cause having a different degree of severity. A research study in the Norwegian construction sector has identified the major risks in project management [85]. Disputes between clients and contractors are most likely to arise and have a negative impact on project performance due to poor communication and cooperation.…”
mentioning
confidence: 99%
“…Given the importance of GBR management during construction, the Emerald Book necessitates an essential role for Engineers who oversee the execution of work on the site [46]. Since large-scale construction projects are generally characterised by conflicts [88], and Engineers play a central role in resolving disputes between parties, their position requires high impartiality. The core functions of the Engineer include assessing the Contractor's execution readiness planning, providing general construction supervision, and supervising and recording excavation work.…”
Section: Dispute Adjudicationmentioning
confidence: 99%